Indwelling voice prosthesis insertion after total pharyngolaryngectomy with free jejunal reconstruction. Issue 1 (24th January 2017) - Fukushima, Hirofumi; Kanazawa, Takeharu; Kawabata, Kazuyoshi; Mitani, Hiroki; Yonekawa, Hiroyuki; Sasaki, Toru; Shimbashi, Wataru; Seto, Akira; Kamiyama, Ryousuke; Misawa, Kiyoshi; Asakage, Takahiro
Abstract : Objectives: Total pharyngolaryngectomy with free jejunal reconstruction is often performed in patients with hypopharyngeal carcinoma. However, postoperative speechlessness significantly decreases patient quality of life. We investigated whether Provox® insertion could preserve speech after total pharyngolaryngectomy with free jejunal reconstruction. Study Design: Retrospective chart review. Methods: A total of 130 cases of secondary Provox® insertions after total pharyngolaryngectomy with free jejunal reconstruction were analyzed. Communication outcomes were compared using the Head and Neck Cancer Understandability of Speech Subscale. Outcomes and complications associated with insertion site (jejunal insertion vs. esophageal insertion) and adjuvant irradiation therapy were also evaluated. Results: Provox® insertion had favorable communication outcomes in 102 cases (78.4%). Neither the insertion site nor irradiation affected the communication outcome. Complications were observed in 20 cases (15.4%). Local infection was the most common complication. Free jejunal insertion, in which the resection range was enlarged, had a lower complication rate than did esophageal insertion, and its complication rate was unaffected by previous irradiation. For all patients, the hospitalization duration and duration of speechlessness were 13.4 days and 14.6 months, respectively. Patients receiving jejunal insertions had a significantly shorter hospitalization duration than did those receiving esophageal insertions. Unlike Provox®2, Provox®Vega significantly reduced the complication rate to zero. Conclusion: For jejunal inserson of a Provox® prosthetic, a sufficient margin can be maintained during total pharyngolaryngectomy and irradiation can be performed, and satisfactory communication outcomes were observed. Provox® insertion after total pharyngolaryngectomy with free jejunal reconstruction should be considered the standard therapy for voice restoration. Level of Evidence: 4.